2020
DOI: 10.1186/s12885-020-06991-2
|View full text |Cite
|
Sign up to set email alerts
|

MassARRAY analysis of twelve cancer related SNPs in esophageal squamous cell carcinoma in J&K, India

Abstract: Background MassARRAY (Agena Bioscience™) combines competitive PCR with MALDI-TOF mass spectrometry (MS) analysis that gives highly accurate, sensitive, and high-throughput methods for the quantitative analysis of variation of gene expression in multiple samples. SNPs (Single Nucleotide Polymorphisms) have a very high potential of discovering disease-gene relationships. SNP-genotyping through MassARRAY is not only a cost-effective genotyping method but also provides a platform to validate variants observed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The results in different races and geographic locations are inconsistent, which may be due to the fact that most studies are local studies with small sample sizes. [18][19][20][21][22][23][24][25][26] Recently, a large-scale prospective study of a homogenous white population from 66 races showed that the GSTP1 Ile105Val (rs1695) genotype is associated with improved lung function and can prevent lung cancer and tobacco-related cancers, 19 which is consistent with the conclusion for the Caucasian population in the Cote et al study. 20 We also assessed the relationship between the GSTP1 Ile105Val gene polymorphism and lung cancer susceptibility through our case-control study of 1979 individuals from the Chinese population, and showed that the GSTP1 rs1695 A > G polymorphism is associated with a reduced risk of lung cancer, especially among smokers.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results in different races and geographic locations are inconsistent, which may be due to the fact that most studies are local studies with small sample sizes. [18][19][20][21][22][23][24][25][26] Recently, a large-scale prospective study of a homogenous white population from 66 races showed that the GSTP1 Ile105Val (rs1695) genotype is associated with improved lung function and can prevent lung cancer and tobacco-related cancers, 19 which is consistent with the conclusion for the Caucasian population in the Cote et al study. 20 We also assessed the relationship between the GSTP1 Ile105Val gene polymorphism and lung cancer susceptibility through our case-control study of 1979 individuals from the Chinese population, and showed that the GSTP1 rs1695 A > G polymorphism is associated with a reduced risk of lung cancer, especially among smokers.…”
Section: Discussionsupporting
confidence: 66%
“…Since Ryberg et al reported that GSTP1 rs1695 A > G polymorphism was related to lung cancer in 1997, 17 many studies have explored the effects of the GSTP1 rs1695 A > G polymorphisms on the risk of lung cancer. [18][19][20][21][22][23][24][25][26] However, there are few studies on the Chinese population, and the results are inconclusive; therefore, it is not enough to draw definite conclusions about the impact of this mutation on the development of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…51206). All these subjects were genotyped by the (Sequenom Mass ARRAY platform) using the 384 well chip according to the standardized protocol which were replicated from the study [21].…”
Section: Genotyping and Quality Controlmentioning
confidence: 99%
“…One recent study has put lung cancer as the second most common cancer in the J&K region with 23.5% of all new cases in 2017 [3]. Although several studies have evaluated mutations in key genes, such as genes involved in cell cycle and cell growth regulation, in DNA damage repair pathways and many other pathways with reference to different cancer types in the population of J&K [4][5][6][7], none has evaluated the role of Translesion Synthesis (TLS) polymerase in any cancer type. The DNA sequence can get altered as the result of replication error and by the environmental agents such as tobacco smoking, mutagenic chemicals, and certain types of radiation, which may lead to cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%